2017
DOI: 10.5116/ijme.58e3.ca8a
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and its association with extracurricular activities among medical students in Saudi Arabia

Abstract: ObjectivesTo assess levels of burnout in medical students, and to explore the influence of extracurricular activities on burnout at a medical school in Saudi Arabia. MethodsThis cross-sectional study was conducted with first to fourth year medical students at King Saud bin Abdulaziz University for Health Sciences (KSAU-HS) in Riyadh, Saudi Arabia. Socio-demographic, burnout level (the Maslach Burnout Inventory-Student Survey, MBI-SS) and participation in extracurricular activities data were collected using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
11
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 34 publications
9
85
11
20
Order By: Relevance
“…On the other hand, numerous studies note lower burnout levels ranging between 10.3% and 45% [16][17][18]. The findings of this research did not match the previous study done by Almalki et al which reported alarming findings and reveal a high burnout level (67%) among medical students [19]. Several factors contribute to these varieties of results.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…On the other hand, numerous studies note lower burnout levels ranging between 10.3% and 45% [16][17][18]. The findings of this research did not match the previous study done by Almalki et al which reported alarming findings and reveal a high burnout level (67%) among medical students [19]. Several factors contribute to these varieties of results.…”
Section: Discussioncontrasting
confidence: 96%
“…This can be due to the high level of knowledge that the relative passes or the early exposure that the student will have. In other studies, students who have a physician among family members show significantly high burnout with high emotional exhaustion and high cynicism [17,19]. Also, another study stated that physicians' parents are the second-highest source of stress for medical students [23].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Stress and burnout, mainly due to heavy schoolwork, progressively developed over the course of medical education (Fares et al, 2016). Appropriate extracurricular activities could reduce anxiety, stress, and burnout and their harmful effects on physical and mental health (Stewart et al, 1997;Almalki et al, 2017;Urlings-Strop et al, 2017). However, our results confirmed that excessive extracurricular activities (>10 h per week) were not positive to SRL level.…”
Section: Time Investment (Time Of Learning Medicine and Extracurriculmentioning
confidence: 43%
“…On the other hand, involvement in other types of leisure activities has different effect on wellbeing and burnout. The involvement in extracurricular activities (extra academic activities such as volunteer/community services, research and teaching activities, reading activities, arts and cultural activities) either is not associated with the burnout level, or may even counteract burnout, especially in college men (Jacobs & Dodd, 2003) and in those leading and organizing extracurricular activities (Almalki, Almojali, Alothman, Masuadi, & Alaqeel, 2017). Extracurricular involvement promotes sense of accomplishment and thus does not lead to emotional exhaustion but play a protective role against low personal accomplishment, one aspect of burnout (Jacobs & Dodd, 2003).…”
Section: Structural Equation Modelingmentioning
confidence: 99%